CompTIA security+TM : exam guide - Conklin, Wm. Arthur [et al] (McGraw Hill New YorkUS, 2011)
Gives an introduction to some of the basic elements of security; includes sections on cryptography and applications; security in the infrastructure and in transmissions; and operational security designed to prepare students to take the CompTIA Security+ certification exam SYO-301.